1999
DOI: 10.1161/01.str.30.3.556
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Impairment Correlates With Hypoperfusion and Hypometabolism but Not With Severity of White Matter Lesions on MRI in Patients With Cerebral Microangiopathy

Abstract: Background and Purpose-Cerebral microangiopathy, indicated on MRI by lacunar infarctions (LI) and deep white matter lesions (DWML), is said to lead to vascular dementia. Methods-Fifty-seven patients with proven cerebral microangiopathy were assessed for changes in regional cerebral blood flow (rCBF) and glucose metabolism (rMRGlu) and compared with 19 age-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
3
12

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 47 publications
7
114
3
12
Order By: Relevance
“…The mild SIVaD group showed a significant reduction in bilateral insula, anterior and posterior cingulate gyrus, precentral gyrus, and subcallosal gyrus and right inferior parietal lobule. This is consistent with the predilection of ischemic lesions, which affect the prefrontal subcortical circuit in VaD, and corresponds to the decreased rCP in the frontal, temporal and parietal lobes, which was previously reported to be observed irrespective of neuropsychological deficit [22].…”
Section: Discussionsupporting
confidence: 91%
“…The mild SIVaD group showed a significant reduction in bilateral insula, anterior and posterior cingulate gyrus, precentral gyrus, and subcallosal gyrus and right inferior parietal lobule. This is consistent with the predilection of ischemic lesions, which affect the prefrontal subcortical circuit in VaD, and corresponds to the decreased rCP in the frontal, temporal and parietal lobes, which was previously reported to be observed irrespective of neuropsychological deficit [22].…”
Section: Discussionsupporting
confidence: 91%
“…(48). Although these observations have not been consistently replicated (49,50), it is reasonable to assume that both the location and the volume of WMLs may influence their effect on regional cortical metabolism and function. (24) It is not clear yet whether the association of WMLs with cortical atrophy and hypometabolism is due to Wallerian degeneration or due to retrograde degeneration and deafferentiation.…”
Section: Histopathologic Correlatesmentioning
confidence: 99%
“…The method allows assessment of the regional cerebral blood flow and volume. Investigators have found that there is a gradation of flow and blood volume in WMLs that decreases from normal tissue on the periphery to reduced values in the center of a lesion (49).…”
Section: Image Acquisitionmentioning
confidence: 99%
“…These results are in agreement with Hund-Georgiadis et al (2002), who reported that morphological changes were not related to neuropsychological impairment in CMA. Further, Sabri et al (1998Sabri et al ( , 1999 showed that, in CMA, neuropsychological deficits correlate with functional imaging parameters such as regional cerebral blood flow and glucose utilization during rest, but not with lacunar infarctions and deep white matter lesions. One may conclude that the latter ones are epiphenomena that may morphologically characterize CMA but do not themselves indicate cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%